Improving Geometry Thinking Ability through Augmented Reality Based Learning Media - Nurbaiti Widyasari; Lulu Irianti Mastura (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
This study aims to improve students' geometrical thinking skills through the media of Augmented Reality learning. Augmented Reality learning media is a learning medium that combines a real object with a virtual object that has a 3-dimensional (3D) shape and is designed to resemble the actual environment that aims to provide any information to its users with an interesting, interactive, and real-time delivery. This study is a quasi-experimental or quasi-experimental study with the design used by researchers, namely the nonequivalent control group design. The population in this study were 202 students of class V SDN Cireundeu 01. The sample of this research was 52 students consisting of 26 experimental class students and 26 control class students who were determined through a purposive sampling technique. The instrument used in this study was in the form of a geometric thinking ability test. Data analysis of students' geometry thinking skills was done by t-test using SPSS 16. The results of the analysis showed that the thinking ability of students in geometry taught using Augmented Reality learning media was higher than students who were taught using concrete media. Therefore the results of this study indicate that mathematics learning by using Augmented Reality learning media has a significant role in increasing students' geometrical thinking abilities